Specific alterations in gut microbiota in patients with chronic kidney disease: an updated systematic review - Zhao, Jin; Ning, Xiaoxuan; Liu, Baojian; Dong, Ruijuan; Bai, Ming; Sun, Shiren (Renal failure, 2021)
Emerging evidence demonstrates that gut dysbiosis is implicated in the pathogenesis of chronic kidney disease (CKD) with underlying mechanisms involving mucosal and/or systematic immunity or metabolic disorders. However, the profile of gut microbiota in patients with CKD has not been completely explored. Databases from their date of inception to 31 March 2020 were systematically searched for case-control or cross-sectional studies comparing the gut microbial profiles in adult patients with CKD or end-stage renal disease (ESRD) with those in healthy controls. Quantitative analysis of alterations in gut microbial profiles was conducted. Twenty-five studies with a total of 1436 CKD patients and 918 healthy controls were included. The present study supports the increased abundance of, phylum Proteobacteria and Fusobacteria, genus Escherichia_Shigella, Desulfovibrio, and Streptococcus, while lower abundance of genus Roseburia, Faecalibacterium, Pyramidobacter, Prevotellaceae_UCG-001, and Prevotella_9 in patients with CKD; and increased abundance of phylum Proteobacteria, and genus Streptococcus and Fusobacterium, while lower abundance of Prevotella, Coprococcus, Megamonas, and Faecalibacterium in patients with ESRD. Moreover, higher concentrations of trimethylamine-N-oxide and p-cresyl sulfate and lower concentrations of short-chain fatty acids were observed. Gut permeability in patients with CKD was not determined due to the heterogeneity of selected parameters. Specific alterations of gut microbial parameters in patients with CKD were identified. However, a full picture of the gut microbiota could not be drawn from the data due to the differences in methodology, and qualitative and incomplete reporting of different studies.